What do Historical Representations Represent? Gnoseological Scepticism between Assertion and Performance - Řezníková, Lenka (Dějiny – teorie – kritika, 2024)
The study is concerned with the question of literary historical representations in fiction around 1900 and towards the end of the 20th century. It compares the nature and form of the gnoseological scepticism about the possibilities and meaning of historical knowledge articulated by writers in both these periods. On the basis of a number of texts from Czech, French and British literature the author shows that the genre known as "historical metafiction", which is one medium for the expression of such scepticism, is not just a product of the later 20th century as might appear from the studies by Linda Hutcheon or Ansgar Nünning. Similar reflective texts had been written at the turn of the 19th/20th century, when in the context of the deepening crisis of historicism, writers had expressed a gnoseological scepticism similar to that of contemporary writers influenced by post-modernism. The writers in the early period employed rather different literary strategies, however, and their transformation can be defined as a shift from assertion to performance.